AUSTRALIA’S RESPONSE TOWARDS KIRIBATI’S MIGRATION WITH DIGNITY POLICY - Rachmawati, Nicky Nastiti; Hidayatullah, Nur Luthfi (SIYAR Journal, 2023)
This study aims to examine the Australian Government's Response towards Kiribati's Migration with Dignity Policy. Rising sea level caused by climate change forces the Pacific Island states, including Kiribati to relocate their citizens overseas. Kiribati launched the Migration with Dignity policy to provide access for its citizens to work in other countries, especially Australia. The authors argue that Australia responded Kiribati’s migration with dignity by providing foreign aid for Kiribati. This study uses a qualitative-descriptive method and utilize the concepts of migration policy and foreign aid, with documentation data collection technique. The results of this study indicate that Australia responded Kiribati’s Migration with Dignity policy by providing foreign aid through the Kiribati Institute of Technology (KIT) and the Kiribati Australia Nursing Initiative (KANI). KIT and KANI opens an opportunity for Kiribati citizens to participate in foreign language and professional skills training, to be able to fulfill Australia’s migration policy requirements for foreign workers.